Hadith #2858 - Sunan Abi Dawud - ibn Abbas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: Whatever is cut off of an animal when it is alive is dead.
Grade: Sahih

Hadith #3022 - Sunan Abi Dawud - al-Hasan bin al-Sbah al-Bzar الحسن بن الصباح البزار; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
When the Prophet (ﷺ) alighted at Marr az-Zahran, al-Abbas said: I thought, I swear by Allah, if the Messenger of Allah (ﷺ) enters Mecca with the army by force before the Quraysh come to him and seek protection from him, it will be their total ruin. So I rode on the mule of the Messenger of Allah (ﷺ) and thought, Perhaps I may find a man coming for his needs who will to the people of Mecca and inform them of the position of the Messenger of Allah (ﷺ), so that they may come to him and seek
Grade: Hasan

Hadith #3149 - Sunan Abi Dawud - al-Hasan bin al-Sbah al-Bzar الحسن بن الصباح البزار; Jabir ibn 'Abdullah; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
That the Messenger of Allah (ﷺ) was shrouded in a garment of Yemeni stuff, it was then removed from him.
Grade: Sahih

Hadith #3867 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) snuffed medicine.
Grade: Sahih

Hadith #4155 - Sunan Abi Dawud - al-Hasan bin al-Sbah al-Bzar الحسن بن الصباح البزار; Jabir ibn 'Abdullah; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: The angels do not enter the house which contains a picture. Busr (b. Sa’id), the transmitter of this tradition, said: Zaid (b. Khalid al-Juhani) then fell it and we paid him a sick visit. There was a curtain with a picture hanging at his door. I then said to ‘Ubaid Allah al-Khawlani’, the step-son of Maimunah, wife of the Prophet (ﷺ): Did Zaid not tell us about pictures on the first day ? ‘Ubaid Allah said: Did you not hear him when he said: Exce
Grade: Sahih

Hadith #5130 - Sunan Abi Dawud - Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hamam bin Munabbih همام بن منبه بن كامل; Sufyan bin 'Uyaynah سفيان بن عيينة; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Your love for a thing causes blindness and deafness.
Grade: Da'if